Analisis hukum islam terhadap arisan julo-julo di desa Paraman Ampalu Pasaman Barat - M. Yarham (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
This study aims to determine the analysis of Islamic law on the Julo-Julo social gathering in Paraman Ampalu Village, Gunung Tuleh District, West Pasaman Regency. This type of research is descriptive qualitative research, using a phenomenological approach. Methods of collecting data through observation, interviews and documentation. The results of this study indicate that the practice of debt and receivables in the practice of Arisan Julo-Julo carried out by the people of Paraman Ampalu Village, Gunung Tuleh District, West Pasaman Regency is illegal. Because, it contains usury nasi'ah, which is exaggerating the payment of goods or money owed due to delays in paying the social gathering money. Then, in terms of the Julo-Julo Arisan Practice contract in Paraman Ampalu Village, Gunung Tuleh District, West Pasaman Regency using a wadi'ah savings contract. The goods deposited are in the form of cash, money deposited by the arisan member to the manager which is then carried out by drawing lots. Furthermore, with regard to the pillars and conditions of the person who makes the deposit and the person who receives the deposit, the person who receives the deposit is the manager, while the person who makes the deposit is the arisan member.